ANALISIS KINERJA SISTEM KAMERA PEMANTAU MENGGUNAKAN SENSOR GERAK DAN BOT TELEGRAM BERBASIS IOT (INTERNET OF THING) - Hendri Syahputra; Ira zulfa; Indra qusyairi (Elkom : Jurnal Elektronika dan Komputer, 2021)
Security is an aspect that is needed by all circles today. With security, it can reduce the risk of crime and worry about the crime. This study discusses a room monitoring camera system using a PIR sensor, if a movement occurs it will be detected by this sensor. To process it, NodeMCU is used, then using the Telegram Bot as a notification if a movement occurs. The way this system works is that the PIR sensor will detect the presence of people or not in the room that is given this security system, then NodeMCU will process the data to send notifications in the form of messages and the IP Camera will display live video broadcasts.